Fast ripple analysis in human mesial temporal lobe epilepsy suggests two different seizure-generating mechanisms - Schönberger, Jan; Frauscher, Birgit; von Ellenrieder, Nicolás; Avoli, Massimo; Dubeau, François; Gotman, Jean (Neurobiology of disease, 2019)
The distinction of hypersynchronous (HYP) and low-voltage fast (LVF) onset seizures in mesial temporal lobe epilepsy (MTLE) is well established, but classifying individual seizures and patients is often challenging. Experimental work indicates a strong association of HYP with fast ripples (250-500Hz) and of LVF with ripples (80-250Hz). We aimed to investigate whether analysis of high-frequency oscillations can be useful for characterizing the process of seizure generation in human MTLE patients. Methods: We retrospectively compared 19 HYP and 14 LVF onset clinical seizures from ten and six consecutive MTLE patients with a predominance of the respective pattern. Five-second intervals of stereotactic EEGs from the seizure onset zone were selected, each representing the onset of HYP and LVF, the corresponding pre-ictal periods and, after the large spikes of HYP onsets, the LVF-like pattern that frequently followed. Results: Pre-ictal fast ripple density and rate were higher for HYP than for LVF seizures (p<.05). This association was also found for initial ictal segments (p<.001). Furthermore, fast ripple density and rate were higher during the LVF-like pattern after HYP spikes than during LVF without preceding HYP (p<.01). Ripple density and rate in contrast did not differ significantly (p>.05). Fast ripple (p<.01) and ripple (p<.001) amplitude was higher during the LVF-like pattern after HYP spikes when compared to LVF without preceding HYP. Significance: Our findings indicate a clear connection between experimental findings and human epilepsy. The association of fast ripples with HYP suggests that out-of-phase firing of different pyramidal cell clusters contributes specifically to generation of these seizures, rather than to LVF onsets. Both during and immediately before seizures, fast ripple analysis may facilitate classification.
Gesehen am 07.08.2019